1993
DOI: 10.1017/s002211209300271x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of periodic flow in curved pipes

Abstract: We have studied oscillatory flow through a 180° curved tube with the ratio of tube radius to radius of curvature equal to 1/7. The flow rate is constrained to vary sinusoidally about a non-zero mean at a specified period T, and mean flow rate Q. At a certain parameter range of interest Hamakiotes & Berger (1990) predict that fully developed flow undergoes a period-tripling bifurcation. Our measurements using laser-Doppler velocimetry found no bifurcation. An additional experiment was done to ensure that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Furthermore, the studies all imposed symmetry across the centreplane of the pipe (the plane containing the centreline of the pipe), so that asymmetric solutions were not permitted. Periodic flows in curved pipes have also been investigated experimentally (Lin & Tarbell 1980;Sudo et al 1992;Swanson, Stalp & Donnelly 1993;Chandran, Yearwood & Wieting 1979). While the above studies all considered curved pipes with zero torsion (so that the pipe centreline remained in the plane), flow in helical pipes has also been considered.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the studies all imposed symmetry across the centreplane of the pipe (the plane containing the centreline of the pipe), so that asymmetric solutions were not permitted. Periodic flows in curved pipes have also been investigated experimentally (Lin & Tarbell 1980;Sudo et al 1992;Swanson, Stalp & Donnelly 1993;Chandran, Yearwood & Wieting 1979). While the above studies all considered curved pipes with zero torsion (so that the pipe centreline remained in the plane), flow in helical pipes has also been considered.…”
Section: Introductionmentioning
confidence: 99%
“…The 1/7 ratio was selected because of its frequent use in the existing body of literature on pulsatile flow through curved geometries. A 180 • bend was similarly selected due to its prevalence in the literature and to ensure that both the axial and secondary flows were developed (Swanson, Stalp & Donnelly 1993). A 3 mm deep recess was machined into each end of the bend apparatus to accommodate the glass tubing, which was affixed to the bend using silicone caulk.…”
Section: • Bend 421 Design Of Bendmentioning
confidence: 99%
“…In pulsatile flow, Talbot & Gong (1983) found that the axial flow separated from the inner wall during deceleration, and they discovered the presence of helical structures in the Dean's vortices. Swanson, Stalp & Donnelly (1993) looked at flow development in curved pipes experimentally and suggested that flow becomes fully developed near 165 • in a 180 • bend. Komai & Tanishita (1997) simulated flow around a curved tube for several curvature ratios, Womersley numbers, and intermittency parameters (ratio of systolic time to the total cardiac period).…”
Section: Introductionmentioning
confidence: 99%
“…Because it was believed that the knowledge of the flow in an arbitrary U tube can contribute to the understanding of the process of arteriosclerosis in a human aorta, the steady and the unsteady flow in a U tube were studied intensively by a number of research groups as early as the early 1970s (23–40). Collins and Dennis published totally developed steady axial velocity profiles (24) for Dean numbers 66.1, 77.1, 190.9, and 369.5.…”
Section: Introductionmentioning
confidence: 99%